Low dose and low dose rate radioluminescence dosimetry - Bradley, D.A. *; Essa, R.Z.; Peh, Suat Cheng *; Teow, Sin Yeang; Chew, Ming Tsuey *; Zubair, H.T.; Oresegun, A.; Azmi, Basaif; Choo, Kan Yeep; Siti A., Ibrahim; Hairul Azhar, Abdul-Rashid (Elsevier, 2023)
Review is provided of a number of low-dose, low dose rate situations that in study require advances in the development of dosimetric facilities. Using a clinical linac set up to provide doses down to the few mGy level, the performance of a real-time radioluminescence system has then been illustrated, accommodating pulsed as well as continuous dose delivery. The system gate times provide for tracking of the pattern of dose delivery, allowing detailed account of dose and dose-rate variations. The system has been tested in both x-ray and electron mode dose delivery.